(untitled) - Graham, Robert J. (Hoboken, New Jersey, 2013)
Does the study of managerial economics make your head spin? This hands-on guide helps you make sense of complex business concepts and explains to you in plain English how managerial economics enhances analytical skills, and assists rational decision making.
Keywords: Managerial economics,Kinh tế quản lý